Synchronous Pulmonary Squamous Cell Carcinoma and Mantle Cell Lymphoma of the Lymph Node. (2nd July 2011) - Sun, Yu; Shi, Yun-Fei; Zhou, Li-Xin; Chen, Ke-Neng; Li, Xiang-Hong
Abstract : Synchronous occurrence of pulmonary squamous cell carcinoma and malignant lymphoma of the lymph node is not reported in the literature. We report a case of pulmonary squamous cell carcinoma coexisting with a mantle cell lymphoma involving cervical and mediastinal lymph node. It is important to recognize this synchronous occurrence histopathologically and to be aware of the existence of "in situ" MCL.